2020
DOI: 10.3390/molecules25235706
|View full text |Cite
|
Sign up to set email alerts
|

On Complex Formation between 5-Fluorouracil and β-Cyclodextrin in Solution and in the Solid State: IR Markers and Detection of Short-Lived Complexes by Diffusion NMR

Abstract: In this work, the nuclear magnetic resonance (NMR) and IR spectroscopic markers of the complexation between 5-fluorouracil (5-FU) and β-cyclodextrin (β-CD) in solid state and in aqueous solution are investigated. In the attenuated total reflectance(ATR) spectra of 5-FU/β-CD products obtained by physical mixing, kneading and co-precipitation, we have identified the two most promising marker bands that could be used to detect complex formations: the C=O and C-F stretching bands of 5-FU that experience a blue shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…Except for the DPC-NS4, all the recorded NMR spectra did not show any significant chemical shift changes from that of 5-FU indicating no complexation with 5-FU. In a recently published study by Melnikova et al, no evidence of complexation was observed between 5-FU and β-cyclodextrin using 1H NMR data ( 29 ).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Except for the DPC-NS4, all the recorded NMR spectra did not show any significant chemical shift changes from that of 5-FU indicating no complexation with 5-FU. In a recently published study by Melnikova et al, no evidence of complexation was observed between 5-FU and β-cyclodextrin using 1H NMR data ( 29 ).…”
Section: Resultsmentioning
confidence: 95%
“…The formulated complexes enhanced the therapeutic efficacy of 5-FU by inhibiting the cell growth of different cell lines ( 31 ). In contrast, a recent study has shown the development of a 5-FU complex with cyclodextrin polymer in an aqueous solution and suggested the formation of an unstable inclusion complex ( 29 ). Moreover, a recent study suggested that cyclodextrin-based nanosponge formulations may be a promising technique for the delivery of 5-FU ( 32 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Many of these techniques are easy to implement as well. When done correctly, NMR can provide truly unique information [2][3][4][5]. The same is with solid state NMR.…”
Section: Introductionmentioning
confidence: 98%